Correlation of silent brain infarcts and leukoaraiosis in middle-aged ischemic stroke patients: a retrospective study - Abdulsalam, Mohammad Fathi; Shaheen, Nour; Shaheen, Ahmed; Alabdallat, Yasmeen Jamal; Ramadan, Abdelraouf; Meshref, Mostafa; Mansour, Fathy Mahmoud; Abed, Elsayed; Fayed, Abdel-Ghaffar I.; Zaki, Mohamed Ahmed; El-Adawy, Ahmad F.; Flouty, Oliver; et al. (Frontiers in Neurology, 2024)
Background Cerebrovascular diseases of the brain are usually defined by transient ischemic attacks and strokes. However, they can also cause brain injuries without neurological events. Silent brain infarcts (SBI) and leukoaraiosis are symptoms of both vascular and neurological abnormalities. This study aims to investigate the association between SBI, leukoaraiosis, and middle-aged patients with ischemic stroke. Methods A single-center retrospective study of 50 middle-aged, ischemic stroke patients were studied from November 2022 and May 2023. The patients were divided into two groups based on the presence or absence of leukoaraiosis. History taking, physical examination, brain CT scan, and MRI were all part of the diagnostic process. Metabolic syndrome (MetS) was also assessed through various factors. The statistical analysis included descriptive statistics, logistic regression analysis, and chi-square test. Results Out of the cohort comprising 50 patients, characterized by a mean age of 52.26 years (SD 5.29), 32 were male, constituting 64% of the sample. Among these patients, 26 individuals exhibited leukoaraiosis, with 17 of them (65.4%) also presenting with SBI. Moreover, within this cohort, 22 patients were diagnosed with MetS, representing 84.6% of those affected. The Multivariate logistic regression analysis showed a strong and independent association between leukoaraiosis and SBI. Individuals with leukoaraiosis were nearly five times more likely to have SBI compared to those without leukoaraiosis. Conclusion The study highlights leukoaraiosis as a significant risk factor for SBI, alongside MetS. Advanced imaging techniques have facilitated their detection, revealing a higher prevalence among stroke patients, particularly associated with age and hypertension. Further research is needed to fully understand their complex relationship and develop better management strategies for cerebrovascular diseases, ultimately improving patient outcomes.